Frequency and Severity of Acute Perineal Skin Reactions in Rectal Cancer Patients at Completion of Preoperative Pelvic Radiotherapy - Sana Mehreen, Aalia Bashir, Muhammad Hisaan Anjum Qadri, Ayesha Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The rectum is the lower part of the colon. Its cancer is the third most common cancer worldwide. Aim: To determine frequency and severity of acute perineal skin reactions in rectal cancer patients at the completion of preoperative pelvic radiotherapy. Study Design: Descriptive case series. Methodology: Study conducted at the Department of Clinical Oncology, Shaukat Khanum Memorial Cancer Hospital Multan. Patients (n=96) were enrolled through non-probability consecutive sampling. All patients received neoadjuvant chemotherapy consisting of fluoropyrimidine and oxaliplatin, Radiotherapy planning was carried out for all patients with a dose of 50.4 Gray in 28 fractions through external beam radiotherapy, consisting of concurrent chemotherapy oral capecitabine twice daily. Severity of skin side effects and were evaluated according to toxicity proforma, based on RTOG/EORTC Toxicity criteria. Data was evaluated by using SPSS vr 23. Poststratification Chi-square test was applied with P-value of 0.05 was considered as significant. Results: Among 96 patients the radiation dermatitis was found in 50(52.08%) patients, grade I treatment toxicity was noted in 27(54%) patients and grade II treatment toxicity was found in 23(46%) patients. Conclusion: It was concluded that patients of rectal carcinoma showed better response rate to concomitant chemo-radiation using Capecitabine with high radiation induced dermal toxicity. Keywords: Rectal Cancer, Oral Capecitabine, Concurrent Chemo-Radiation and Skin toxicity.